PERANCANGAN PROTOTYPE APLIKASI PEMESANAN PERCETAKAN MENGGUNAKAN ALGORITMA WHATSAPP GATEWAY PADA PT MONICA INTERMEDIA GRAFIKA - Ahmad Asyhadi (Jurnal Processor, 2021)
The printing purchase order (PO) information system uses the WhatsApp gateway, which aims to provide PO Printing and customer invoicing services. This time, PT MIG is engaged in graphics, which already has regular customers and print routines. The problem that often occurs is the management of customer transactions, where customers make print orders using WhatsApp Messenger more often. So that the admin has difficulty recording it, because the message is deleted or forgot to write it down. The design of this system uses UML (Unified Modeling Language) tools with the Prototype model. Keywords : Prototype, PO Printing, Whatsapp Gateway.